2021
DOI: 10.3390/ijerph18094700
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural Influences on the Feeling of Loneliness of Family Caregivers of People with Dementia: The Role of Kinship

Abstract: The extent to which familism, dysfunctional thoughts, and coping variables contribute to explaining feelings of loneliness in caregivers, controlling for kinship, is analyzed. Participants were 273 family caregivers of people with dementia. Sociodemographic variables, familism, dysfunctional thoughts, coping strategies for requesting and receiving help, perceived social support, and leisure activities were assessed. The fit of a theoretical model for explaining the effect of cultural and psychological variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
1
12
0
4
Order By: Relevance
“…We further found that reduced frequency of leisure activities significantly mediated the direct effect of dysfunctional thoughts on IL-6 levels. These results support prior literature, according to which dysfunctional thoughts may act to directly reduce engagement in leisure activities (34,35). The results also support prior evidence that reduced engagement in leisure activities is associated with inflammatory processes in the dementia caregiver population (31).…”
Section: Discussionsupporting
confidence: 91%
“…We further found that reduced frequency of leisure activities significantly mediated the direct effect of dysfunctional thoughts on IL-6 levels. These results support prior literature, according to which dysfunctional thoughts may act to directly reduce engagement in leisure activities (34,35). The results also support prior evidence that reduced engagement in leisure activities is associated with inflammatory processes in the dementia caregiver population (31).…”
Section: Discussionsupporting
confidence: 91%
“…As suggested by Huertas‐Domingo et al. (2021), caregivers' sons usually care for a mother and do not have additional sources of aid for caregiving duties (e.g., a wife or a sister) 10 …”
Section: Discussionmentioning
confidence: 99%
“…As suggested by Huertas-Domingo et al (2021), caregivers' sons usually care for a mother and do not have additional sources of aid for caregiving duties (e.g., a wife or a sister). 10 Results are novel in indicating that depressive symptomatology in daughter caregivers may be related to concomitant medical conditions. They may be an especially vulnerable subgroup to receive medical and psychological care.…”
Section: Discussionmentioning
confidence: 99%
“…While being a spouse carer of PwD is associated with a variety of health outcomes, caring also affects their well-being and psychosocial situation. For instance, spouse carers of PwD experience higher levels of loneliness and social isolation than both non-spouse carers of PwD and other informal carers [16][17][18] and may withdraw from social situations after experiencing shame due to their partner's dementia-related behaviours [19]. In addition, spouse carers of PwD can experience feelings that their future is uncertain, that their life lacks meaning, or be filled with grief due to the progressive loss of their partner to dementia [19,20].…”
Section: Factors Associated With Outcomes Of Carementioning
confidence: 99%